A study in interactive 3-D rotation using 2-D control devices - Sellen, Abigail (Computer Graphics, 1988)
This paper describes and evaluates the design of four virtual controllers for use in rotating three-dimensional objects using the mouse. Three of four of these controllers are "new" in that they extend traditional direct manipulation techniques to a 3-D environment. User performance is compared during simple and complex rotation tasks. The results indicate faster performance for complex rotations using the new eontinuoos axes controllers compared to more traditional slider approaches. No significant differences in accuracy for complex rotations were found across the virtual controllers. A second study compared the best of these four virtual controllers (the Virtual Sphere) to a control device by Evans, Tanner and Wein. No significant differences either in time to complete rotation task or accuracy of performance were found. All but one subject indicated they preferred the Virtual Sphere because it seemed more "natural".